Neurociencias, etología humana y educación: una mirada antropológica (2019)
This paper revolves around the integrating dialectical relationship between the neurosciences of education, human ethology of the last decades and their contribution to the question of modernity What is man? From the initial postulates of Morin, going through the anthropological view of Gehlen and collecting the empirical findings of brain development in the early years, the proposal seeks to raise a bridge between concepts of development and pedagogy proposed by Kant. That is to say, the one of an unfinished being that is constructed from education and pedagogy from the contribution of the social thing.